“Cinderella” Vs “Timun Mas”: Exploring Gender Stereotypes and Culture as Learning Material Purposes - Cynantia Rachmijati; Sri Supiah Cahyati (Pusat Studi Bahasa dan Publikasi Ilmiah, 2021)
Gender roles are an important part of culture. How the genders are portrayed in the literature contributes to the image young adults develops of their gender roles and the role of gender in the social order. This research entitled “Cinderella VS Timun Mas : Exploring gender stereotypes and culture as learning materials purposes” aimed to analyze the content of both “Cinderella” and “Timun Mas” which cover: 1. Occupations and Gender Stereotypes; 2 Centrality of Female and Male Characters; 3. Culture Content ; and 4 Suitability as learning material purposes. This research is a qualitative study using content analysis. It was carried out with procedures: collecting, analyzing, and presenting data. Based on research questions it is revealed that for occupation and gender types showed that “Timun mas” has varieties of gender with 66,67% reference whereas “Cinderella” only has 50% references. For the centrality of male and female character, “Cinderella’ has more varieties in 37,5% male and 62,5% female whereas in “Timun Mas” showed 50% for both genders”. For the cultural content, in “Timun Mas” the cultural content found was 60% and in “Cinderella” was 80%. And the suitability to be used as learning materials showed that “Timun Mas” checked with 16 points whereas “Cinderella” checked with 20 points. It can be concluded that both can be used as authentic learning materials for gender references, but “Cinderella” has more varieties and cultural content compared to “Timun Mas”.